Reflexões sobre a formação inicial de professores de química do agreste sergipano: contribuições das atividades - Santos, Gladston dos (2013)
Limits on teacher training are present in the discussions and evaluations of students, due to the way that the subjects are covered in class, making them difficult to understand. This may have been caused due to the initial training of these teachers. Therefore, to occur the individual s participation in society, it is necessary that the teacher builds a bond being content and everyday school student. The study of chemistry is mainly due to the fact enable man to develop a critical view of the world taking notice of conditions and interfere with situations that contribute to their quality of life. One of the ways that the school with the teacher can allow the experience of real situations and visualization of phenomena is through experimental activities, which allows students feel encouraged to attend, to participate in the classes, thus performing the activities in conjunction with the teacher, thus enabling active participation of students. Therefore, this study aimed to analyze and reflect on how it undertook initial training of teachers of Chemistry UFS Campus Itabaiana UP, and what were the contributions they have had on graduation to be able to develop and execute experimental activities in lessons basic education, this question arises precisely because the researcher was student from the first class of this course. The data obtained from the questionnaires were analyzed and tabulated enabling the creation of a focus group that could identify more concrete data on the contributions that the trial provided the graduates then were drawn dimensions and categories. An important point raised was that the experimental activities carried out at the University are decontextualized and contributed little in training these future teachers. Thus, it is important that, at graduation, a time for discussions and applications of experimental activities with nature to basic education